THE INFLUENCE OF MICRO-FINANCE SCHEMES ON THE INVESTMENT PATTERN OF RURAL PEOPLE IN ALAPPUZHA (International Journal of Food and Nutritional Sciences, 2022)
Investment is the backbone of any person’s success. It is the process that supports wealth creation. As far as a rural family is concerned, even a small investment decision is more important than any other life decision. In India, where much of the rural population lives below the poverty line, it is crucial to develop an investment habit among the rural people to find a sustainable livelihood. "Micro-finance is the delivery of a wide range of financial services to low-income households and their microbusinesses, including deposits, loans, payment services, money transfers, and insurance." (Sharma 2001)1. Micro-finance has been recognised as a tool for poverty eradication. Services provided by micro-finance institutions and NGOs are somewhat helping rural people to fight poverty. The investment pattern of rural people also helps them to fight poverty. The researcher has attempted to study whether there is any relation between the micro-finance schemes introduced in rural areas of Alappuzha district and the investment patterns of the same people. The stratified random sampling method has been used for selecting the sample. A survey method using an interview schedule has been employed for collecting primary data from 150 respondents who are the users of micro-finance schemes in rural areas of Alappuzha district. The collected data has been analysed and interpreted using descriptive analysis, the independent sample t test, the chi-square test, and one sample T test to arrive at proper conclusions. The research paper concludes that micro-finance schemes significantly influence the investment patterns of rural people in Alappuzha district.